Nursing interventions prescribed for adult patients admitted to intensive care unit - Kalliny de Oliveira Nathiara Stralhoti; Fabiana Gonçalves de Oliveira Azevedo Matos; Débora Cristina Ignácio Alves; João Lucas Campos de Oliveira; Djulia Camila Berwanger; Drieli Wawzeniak de Anchieta (Universidade Federal de Santa Maria, 2019)
Objective: to identify the nursing interventions prescribed for adult patients hospitalized in the Intensive Care Unit. Method: documentary, cross-sectional and cross-mapping study conducted at a public teaching hospital. A total of 29 records with nursing prescriptions at the patient's admission to the unit were evaluated. The prescribed interventions (n = 725) were mapped according to Nursing Interventions Classification and analyzed using descriptive statistics. Results: The 725 prescribed interventions were in 18 "nursing interventions", nine "classes" and three "domains". The interventions "Skin/wound care", "Pressure Management", "Monitoring" and "Infection Control"; the classes "Skin/Wound Management" and "Self-Care Facilitation" and "Complex Physiological" and "Basic Physiological" domains were the most frequent. Conclusions: the prescriptions made by intensive care nurses were related to the promotion and maintenance of human physiological and safety needs. Descriptors: Nursing; Nursing Process; Critical Care; Classification; Intensive Care Units